Application of thermosensitive-hydrogel combined with dental pulp stem cells on the injured fallopian tube mucosa in an animal model - Luo, Lihua; Zhu, Qunyan; Li, Yejian; Hu, Fengting; Yu, Jiangtao; Liao, Xiangyan; Xing, Zhenjie; He, Yan; Ye, Qingsong (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives: Fallopian tube (FT) injury is an important factor that can lead to tubal infertility. Stem-cell-based therapy shows great potential for the treatment of injured FT. However, little research has shown that mesenchymal stem cells (MSCs) can be used to treat FT damage by in situ injection. In this study, we in situ transplanted PF127 hydrogel encapsulating dental pulp stem cells (DPSCs) into the injured sites to promote the repair and regeneration of FT injury. Materials and methods: The properties of DPSCs were evaluated by flow cytometry, immunofluorescence analysis, and multi-differentiation detection. The immunomodulatory and angiogenic characteristics of DPSCs were analyzed on the basis of the detection of inflammatory factor expression and the formation of capillary-like structures, respectively. The biocompatibility of PF127 hydrogel was evaluated by using Live/Dead and CCK-8 assays. The effects of PF127 hydrogel containing DPSCs on the repair and regeneration of FT injury were evaluated by histological analysis (e.g., hematoxylin and eosin (H&E) and Masson’s trichrome staining, TUNEL staining, immunofluorescence staining, and immunohistochemistry), Enzyme-linked immunosorbent assay (ELISA), and RT-PCR detections. Results: DPSCs had MSC-like characteristics and great immunomodulatory and angiogenic properties. PF127 hydrogel had a thermosensitive feature and great cytocompatibility with DPSCs. In addition, our results indicated that PF127 hydrogel containing DPSCs could promote the repair and regeneration of FT damage by inhibiting cell apoptosis, stimulating the secretion of angiogenic factors, promoting cell proliferation, modulating the secretion of inflammatory factors, and restoring the secretion of epithelial cells. Conclusions: In this study, our results reported that in situ injection of PF127 hydrogel encapsulating DPSCs into the injured sites could provide an attractive strategy for the future treatment of FT injury in clinical settings.